Introductory Remarks - Migdal, Ariela (Columbia Journal of Gender and Law, 2013)
Thank you, Katherine Franke, for your kind introduction and to the Columbia Law School Center for Gender and Sexuality Law for hosting this event. I am privileged to moderate this conversation among distinguished scholars and activists, each of whom will offer a unique perspective on the women’s rights litigation of the 1970s. Justice Ginsburg spearheaded this litigation campaign, in collaboration with a number of our panelists. And I am tremendously honored to be part of this event celebrating Justice Ginsburg. As attorneys at the ACLU’s Women’s Rights Project, my colleagues and I, under the leadership of our director Lenora Lapidus, try to carry forward the work of these litigators and scholars. I’m grateful for this opportunity to reflect on all that women’s rights litigators achieved during that era, and to think about how we can most effectively build on those accomplishments to advance the cause of gender equality. When I reflect on the groundbreaking litigation that our panelists undertook in the 1970s, I confront a paradox. On one hand, I am acutely aware of their revolutionary accomplishments in exposing and ultimately overturning a web of laws and practices that limited women’s equality. Yet, as a litigator and advocate, I spend most of my energy focusing on the remaining, entrenched inequality and devising ways to combat it. When I come to work in the morning, I focus on the part of the glass that is half empty.